The Effect of Current Strength Towards ABREX Steel 400 Pulling Strength by Using SMAW Welding with Electrode E7018 - Rizki, Muhammad; Erizon, Nelvi; Syahri, Budi; jr, Rodger Eliab (Teknomekanik, 2020)
The aim of this study is to determine the effect of variations in welding current strength on the tensile strength of ABREX 400 steel weld joints. The results of this study are expected to give contribution toward the world of metal welding, especially low carbon steel metal welding which will later be beneficial for the development of the metal industry and technology. The method used in this research was the experimental method. In addition, the process of welding the material used SMAW welding and the type of seam V connection and the variations in the current strength used are 90 A, 100 A, and 110 A. The specimen used was a TRS 400 low carbon steel plate with a thickness of 10 mm and the electrode used was the E7018 electrode Ø 3.2 mm. The standard specimen used was ASTM-8 and the test was carried out using the Universal Testing Machine tensile test device. As a result, the research showed that the tensile strength at a current of 90 A was 588.91 N / mm2, a current of 100 A was 570.56 N / mm2, and a current of 100 A was 545.17 N / mm2. Based on the results of the research, it can be concluded that welding using a current strength of 90 A produces the highest tensile strength value, namely 588.91 N / mm2 compared to currents of 100 A and 110 A.